The Effect of Competence and Work Discipline on Employee Performance with Job Satisfaction Mediation - Oktaf Saputra; Tristiana Rijanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of competence and work discipline on employee performance with job satisfaction as a mediating variable. The study was conducted on employees of the Public Order Agency (Satpol PP) and the Semarang Regency Fire Department. A total of 106 respondents were selected using purposive sampling techniques based on certain criteria. The research method used was quantitative with a survey approach. Data collection was carried out through questionnaires and analyzed using multiple linear regression and the Sobel test. The results showed that competence had no effect on either job satisfaction or performance. Work discipline had a positive and significant effect on job satisfaction. Work discipline had no effect on employee performance. Job satisfaction had an effect on employee performance. Job satisfaction did not mediate the effect of competence on employee performance. Job satisfaction mediated the effect of work discipline on employee performance.